URGENSI PENDIDIKAN KARAKTER DI MIN 1 PROBOLINGGO - Feriska Listrianti (Nurul Jadid University, 2019)
This paper presents the urgency of implementing character education at MIN 1 Probolinggo. Based on the various phenomena that exist about the moral degradation of the nation's children which are currently rife, there is a lack of honesty during the exam. MIN 1 Probolinggo as an educational institution implements character education because educational institutions are playing environments and where children interact long enough to influence their character education. MIN 1 Probolinggo in its application through several steps, namely, planting monotheism, adab, responsibility, caring, independence and community. MIN 1 Probolinggo provides provisions in the form of character education for MI-level children that are easy to remember and implement in everyday life.